Medical cannabis for the treatment of comorbid symptoms in children with autism spectrum disorder: An interim analysis of biochemical safety - Stolar, Orit; Hazan, Ariela; Vissoker, Roni Enten; Kishk, Ibrahim Abu; Barchel, Dana; Lezinger, Mirit; Dagan, Adi; Treves, Nir; Meiri, David; Berkovitch, Matitiahu; Kohn, Elkana; Heyman, Eli (Frontiers in Pharmacology, 2022)
Background: Autistic Spectrum Disorder (ASD) is a common neurodevelopmental disorder and no effective treatment for the core symptoms is currently available. The present study is part of a larger clinical trial assessing the effects of cannabis oil on autism co-morbidities. Objectives: The aim of the present study was to assess the safety of a CBD-rich oil treatment in children and adolescents with ASD. Methods: Data from 59 children and young adults (ages 5–25 years) from a single-arm, ongoing, prospective, open-label, one center, phase III study was analyzed. Participants received the Nitzan Spectrum® Oil, with cannabis extracts infused in medium chain triglyceride (MCT) oil with a cannabidiol:THC ratio of 20:1, for 6 months. Blood analysis was performed before treatment initiation, and after 3 months. Complete blood count, glucose, urea, creatinine, electrolytes, liver enzymes (AST, ALT, gamma glutamyl transferase), bilirubin, lipid profile, TSH, FT4, thyroid antibodies, prolactin, and testosterone measurements were performed at baseline, prior to starting treatment and at study midpoint, after 3 months of treatment. Results: 59 children (85% male and 15% female) were followed for 18 ± 8 weeks (mean ±SD). The mean total daily dose was 7.88 ± 4.24 mg/kg body weight. No clinically significant differences were found in any of the analytes between baseline and 3 months follow up. Lactate dehydrogenase was significantly higher before treatment (505.36 ± 95.1 IU/l) as compared to its level after 3 months of treatment (470.55 ± 84.22 IU/L) (p = 0.003). FT4 was significantly higher after 3 months of treatment (15.54 ± 1.9) as compared to its level before treatment (15.07 ± 1.88) (p = 0.03), as was TSH [(2.34 ± 1.17) and (2.05 ± 1.02)] before and after 3 months of treatment, respectively (p = 0.01). However, all these values were within normal range. A comparison of the group with additional medications (n = 14) to those who received solely medical cannabis (n = 45) showed no difference in biochemical analysis, including liver enzymes, which remained stable, except for change in potassium level which was significantly higher in the group that did not receive additional medications (0.04 ± 0.37) compared to the group receiving concomitant drug therapy (-0.2 ± 0.33) (p = 0.04). A comparison of patients who received a high dose of the cannabis oil (upper quartile-16 patients), with those receiving a low dose (lower quartile—14 patients) showed no significant difference between the two groups, except for the mean change of total protein, which was significantly higher among patients receiving high dose of CBD (0.19 ± 2.74) compared to those receiving a low dose of CBD (1.71 ± 2.46 (p = 0.01), and mean change in number of platelets, that was significantly lower among patients who received high dose of CBD (13.46 ± 31.38) as compared to those who received low dose of CBD (29.64 ± 26.2) (p = 0.0007). However, both of these changes lack clinical significance. Conclusion: CBD-rich cannabis oil (CBD: THC 20:1), appears to have a good safety profile. Long-term monitoring with a larger number of participants is warranted.